STRATEGI KOMUNITAS INFORMASI MASYARAKAT (KIM) MEDIA PAHARI DIPAH DALAM MENYAMPAIKAN INFORMASI KEPADA MASYARAKAT KELURAHAN MENTAYA SEBERANG KECAMATAN SERANAU: Strategy of Public Information Community (KIM) Media Pahari Dipah In Conveying Information To The Community Of Mentaya Seberang Village Seranau District - Junaidi, Junaidi; Rusdiansyah, Rusdiansyah; Saipul, Saipul (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2025)
Community Information Group (KIM) or other similar groups are groups formed by, from, for the community independently and creatively whose activities are managing information and empowering the community in order to increase added value. This study aims to see how the Community Information Community (KIM) of Media Pahari Dipah, Mentaya Seberang Village, Seranau District, East Kotawaringin Regency, Central Kalimantan, is able to play a role as a model of community participation in information disclosure for the community at the Seranau District level. So that the community plays an active role, cares, is sensitive and understands information, can choose and sort the information needed and two-way communication media between the community and the community and the community with the government, through print media, electronic media and social media. Then receive, filter and detect information circulating in the community, by utilizing the Community Information Community (KIM) of Mentaya Seberang Village, as a medium for information in digital information transactions. The approach in this study uses a descriptive qualitative approach. This study shows that it has succeeded in finding 4 main stages of answers to the Community Information Community Strategy (KIM) of Pahari Dipah Media, Mentaya Seberang Village, Seranau District, namely for the KIM chairman and members to always be active and not passive in publishing the existence of KIM in the Seranau District area, to continue to coordinate with the Village, District and related Offices, in terms of minimal budget in KIM management, it can be done independently either with fellow KIM administrators, always trying to utilize digital services created by the Communication and Informatics Office of East Kotawaringin Regency in the form of an official address account kotimkab.go.id. As a means of disseminating information to the community in Seranau District.